Normative-Legal and Conceptual Principles of Cooperation of Social Pedagogue with Family as for the Education of Sex of Pupils-Teenagers - Anna Prykhodko (Pedagogical Discourse, 2017)
The article is devoted to normative-legal and conceptual principles of the partnership of social teacher and family in the process of education of teenagers’ sex. The main theoretical bases of normative and legal regulation of an educational sphere, the partnership of social teacher and family of teenagers in it are analyzed and systematized in the article. The author describes some modern normative-legal documents in the contents of that are determined terms, principles and mechanisms of a consolidation of efforts of family with the representatives of educational establishments, in particular social teacher in the process of education of teenagers’ sex. Much attention is given to those state documents positions, which touch upon a concept «social partnership», it planning and the organization in the aspect of education of teenagers’ sex at general school.It should be stressed that the author understands a concept «education of teenagers’ sex» as a process of forming of certain personal constructs, a system of moral options and norms in the field of interpersonalшен contacts with representatives their own and opposite sex. The work also has analyzed legislative initiatives concerning to a consolidation of efforts of social teacher with family of teenagers. Also the procedure of normative and legal regulation of the partnership between social teacher and family in the process of education of teenagers’ sex was disclosed in the paper. The author stresses that the effective partnership of social teacher and family it’s a basic mechanism of making of only requirements to the organization and the realization of the process of education of teenagers’ sex in their study at general school, during after-hour, cultural and leisure-time activity, and in the process of the establishment of productive intersexual cooperation on the whole.